The impact of post-traumatic stress disorder symptomatology on quality of life: The sentinel experience of anger, hypervigilance and restricted affect. (April 2019) - Forbes, David; Nickerson, Angela; Bryant, Richard A; Creamer, Mark; Silove, Derrick; McFarlane, Alexander C; Van Hooff, Miranda; Phelps, Andrea; Felmingham, Kim L; Malhi, Gin S; Steel, Zachary; Fredrickson, Julia; et al.
Background: It is unclear which specific symptoms of post-traumatic stress disorder are related to poor perceived quality of life. Objective: To investigate the influence of post-traumatic stress disorder symptomatology on quality of life in traumatic injury survivors. Method: Traumatic injury survivors completed questionnaires on post-traumatic stress disorder symptomatology and quality of life at 3 months ( n = 987), 12 months ( n = 862), 24 months ( n = 830) and 6 years ( n = 613) post trauma. Results: Low quality of life was reported by 14.5% of injury survivors at 3 months and 8% at 6 years post event. The post-traumatic stress disorder symptom clusters that contributed most to poor perceived quality of life were numbing and arousal, the individual symptoms that contributed most were anger, hypervigilance and restricted affect . Conclusions: There was variability in the quality of life of traumatic injury survivors in the 6 years following trauma and a consistent proportion reported low quality of life. Early intervention to reduce anger, hypervigilance and restricted affect symptoms may provide a means to improving the quality of life of traumatic injury survivors.